2019
DOI: 10.7717/peerj.7047
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric ratios support plant adaption to grazing moderated by soil nutrients and root enzymes

Abstract: Background Vegetation succession is one of the major driving processes of grassland degradation. Stoichiometry significantly contributes to vegetation dynamics. However, a knowledge gap exists in how soil nutrients and root enzymes influence the stoichiometric ratio to affect vegetation dynamics. Methods To address these questions, we selected a dominant species (Leymus chinensis (Trin.) Tzvel.) and a degraded-dominant species (Artemisia fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 76 publications
4
8
0
Order By: Relevance
“…The findings from this study reveal that overgrazing significantly increased the N concentration in the green leaves of the dominant species investigated. This corroborates earlier reports (Bai et al, 2012;Ma et al, 2019) that herbivore grazing modifies plant N concentration. Compared with the grazing exclusion plot, the high green leaf N concentration recorded for the dominant species (L. chinensis, S. grandis, and C. squarrosa) in the long-term grazing plot may be attributed to increased synthesis of protein by the ribosome to aid plant growth after successive grazing (Elser et al, 2000;Ma et al, 2019).…”
Section: Effects Of Overgrazing On the Leaf Nutrient Statussupporting
confidence: 93%
See 1 more Smart Citation
“…The findings from this study reveal that overgrazing significantly increased the N concentration in the green leaves of the dominant species investigated. This corroborates earlier reports (Bai et al, 2012;Ma et al, 2019) that herbivore grazing modifies plant N concentration. Compared with the grazing exclusion plot, the high green leaf N concentration recorded for the dominant species (L. chinensis, S. grandis, and C. squarrosa) in the long-term grazing plot may be attributed to increased synthesis of protein by the ribosome to aid plant growth after successive grazing (Elser et al, 2000;Ma et al, 2019).…”
Section: Effects Of Overgrazing On the Leaf Nutrient Statussupporting
confidence: 93%
“…Interestingly, SAP is higher in the long-term grazing than the grazing exclusion plot. This implies that the decomposition of faeces and urine in the long-term grazing plot enhanced the faster release of P into the soil (Ma et al, 2019), which makes more P available through microbial mineralization for plants uptake (Chen et al, 2004). Therefore, grazing can increase green leaf P concentration indirectly.…”
Section: Effects Of Overgrazing On the Leaf Nutrient Statusmentioning
confidence: 99%
“…However, the stocking rate recommended by the local government is ∼1.5 sheep units per hectare to achieve a balance between grassland productivity and livestock forage requirements. Thus, the continuously grazed plot has experienced heavy grazing pressure over the last several decades (Ma et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…So far, a large number of croplands have been converted to natural grassland or forest in the Loess Plateau. Soil nutrient concentrations generally undergo dynamic changes over time, and these changes directly influence elemental nutrient stoichiometry (Fan et al, 2015;Ma et al, 2019;Wang et al, 2014). Many studies have found that vegetation restoration enhances soil nutrient status, improves microbial activity (Fan et al, 2015;Ren et al, 2016;Zinn, Marrenjo & Silva, 2018), and improves the C:N:P stoichiometry (Bai et al, 2019;Yang & Luo, 2011).…”
Section: Introductionmentioning
confidence: 99%